Review of Reported Clinical Information System Adverse Events in US Food and Drug Administration Databases - Myers, R.B.; Jones, S.L.; Sittig, D.F. (Applied Clinical Informatics, 2011)
Background: The US FDA has been collecting information on medical devices involved in significant adverse advents since 1984. These reports have been used by researchers to advise clinicians on potential risks and complications of using these devices.Objective: Research adverse events related to the use of Clinical Information Systems (CIS) as reported in FDA databases.Methods: Three large, national, adverse event medical device databases were examined for reports pertaining to CIS.Results: One hundred and twenty unique reports (from over 1.4 million reports) were found, representing 32 manufacturers. The manifestations of these adverse events included: missing or incorrect data, data displayed for the wrong patient, chaos during system downtime and system unavailable for use. Analysis of these reports illustrated events associated with system design, implementation, use, and support.Conclusion: The identified causes can be used by manufacturers to improve their products and by clinical facilities and providers to adjust their workflow and implementation processes appropriately. The small number of reports found indicates a need to raise awareness regarding publicly available tools for documenting problems with CIS and for additional reporting and dialog between manufacturers, organizations, and users.
Keywords: Electronic health records; information systems; mandatory reporting; medical errors; United States Food and Drug Administration